2018
DOI: 10.1021/acs.iecr.8b01617
|View full text |Cite
|
Sign up to set email alerts
|

Separation of the Methanol–Ethanol–Water Mixture Using Ionic Liquid

Abstract: Vapor pressure data for the binary systems (water/methanol/ethanol + 1-ethyl-3-methylimidazolium acetate ([EMIM]+[Ac]−)) and the ternary systems (methanol + water + [EMIM]+[Ac]−, ethanol + water + [EMIM]+[Ac]−, and methanol + ethanol + [EMIM]+[Ac]−) were measured by a modified equilibrium still. For the above systems, the maximum average relative deviation between experimental data and the UNIFAC-Lei model predicted values was 7%, confirming the prediction accuracy of the UNIFAC-Lei model. Thus, this model was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 71 publications
(86 reference statements)
0
32
0
1
Order By: Relevance
“…The inherent high thermal stability, good affinity with polar gases, and nonvolatility make ILs promising candidates as robust gas‐responsive materials and ILs are widely explored in fields of gas capture, gas sensing, and gas separation. [ 48–50 ] Generally, ILs are able to capture gases via van der Waals interactions or hydrogen bondings between them, and the change of their properties, such as conductivity and viscosity, can be utilized to detect and monitor the captured gases.…”
Section: Il‐based Gas‐responsive Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…The inherent high thermal stability, good affinity with polar gases, and nonvolatility make ILs promising candidates as robust gas‐responsive materials and ILs are widely explored in fields of gas capture, gas sensing, and gas separation. [ 48–50 ] Generally, ILs are able to capture gases via van der Waals interactions or hydrogen bondings between them, and the change of their properties, such as conductivity and viscosity, can be utilized to detect and monitor the captured gases.…”
Section: Il‐based Gas‐responsive Materialsmentioning
confidence: 99%
“…[13][14][15][16][17][18][19][20][21][22][23][24][25] The developments of advanced smart sensing, and gas separation. [48][49][50] Generally, ILs are able to capture gases via van der Waals interactions or hydrogen bondings between them, and the change of their properties, such as conductivity and viscosity, can be utilized to detect and monitor the captured gases.…”
Section: Introductionmentioning
confidence: 99%
“…For designing the extractive distillation process to recover TFP from its aqueous solution, the vapor phase is assumed as an ideal gas. The NRTL model is adopted to describe the non-ideality of liquid phase, which is usually applied to correlate the vapor-liquid equilibrium (VLE) data concerning the ILs compared to the predictive UNIFAC 31 and UNIFAC-Lei 24 models. The binary interaction parameters of the NRTL model for IL-TFP, IL-water, 30 and TFP-water 5 are listed in Supporting Information, Table S1.…”
Section: Conceptual Designmentioning
confidence: 99%
“…Meanwhile, liquid-liquid extraction was used to separate the mixture of TFP and water by Xu et al 17 and Li et al 18,19 Combining the advantages of extraction and distillation, Shen and Chien 20 provided a hybrid extraction-distillation flowsheet for separating TFP and water with energy savings. Recently, ionic liquids (ILs) as green solvents have been applied as entrainers to replace traditional organic solvents in extractive distillation [21][22][23][24][25][26] because of their negligible vapor pressure, high selectivity, and low toxicity. [27][28][29] In this paper, three extractive distillation processes with 1-ethyl-3-methylimidazolium acetate ([EMIM][Ac]) as a proper entrainer are designed based on the previous experimental work, which has shown that IL [EMIM][Ac] can effectively eliminate the azeotropic point of the mixture TFP and water.…”
Section: Introductionmentioning
confidence: 99%
“…[143][144][145][146][147][148] . H αμελητέα τάση ατμών τους, το μεγάλο θερμοκρασιακό εύρος στο οποίο παραμένουν στην υγρή φάση σε συνδυασμό και με τη μη ευφλεκτικότητα, αποτέλεσε το έναυσμα για την αύξηση του ενδιαφέροντος σχετικά με την εφαρμογή τους σε διεργασίες διαχωρισμού μιγμάτων [149][150][151][152][153][154][155][156][157][158][159][160][161][162][163][164][165][166][167][168] , στην εκχύλιση [169][170][171][172][173][174] , στην απορρόφηση αερίων [175][176][177][178][179][180] (π.χ. CO2).…”
Section: εφαρμογές ιοντικών υγρώνunclassified